Globalisation Of Islamic Education In Southeast Asia - Abdul Hamid, Ahmad Fauzi (2009)
The millennial advent of a Global War on Terrorism (GWOT), pursued by the United States of America (USA) in the wake of devastating terrorist attacks on the World Trade Centre in New York and the Pentagon on 11 September 2001 (hereafter 9111), cast gloom on the prospects of inter-cultural and inter-religious dialogue in an increasingly interdependent world. The USA's conduct of GWOT has been subjected to various censures by analysts for being over-militaristic, neglecting ideological warfare and uncritically aggregating disparate trends of terrorism.